2013
DOI: 10.1534/genetics.112.148098
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Chaperone HSP90 Can Facilitate the Divergence of Gene Duplicates

Abstract: The heat-shock protein 90 (HSP90) acts as a chaperone by ensuring proper maturation and folding of its client proteins. The HSP90 capacitor hypothesis holds that interactions with HSP90 allow proteins to accumulate mutations while maintaining function. Following this logic, HSP90 clients would be predicted to show relaxed selection compared with nonclients. In this study, we identify a new HSP90 client in the plant steroid hormone pathway: the transcription factor BES1. Its closest paralog, BZR1, is not an HSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
69
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 70 publications
10
69
0
Order By: Relevance
“…Recently, Samakovli et al (2014) reported that HSP90 interacts with a BR signaling component, BIN2 kinase, to modulate its nuclear retention. Independently of their study, HSP90 was also found to bind to BES1 (Lachowiec et al, 2013;Shigeta et al, 2014). These findings suggest the involvement and importance of HSP90 activity in BR signaling.…”
Section: Introductionmentioning
confidence: 80%
“…Recently, Samakovli et al (2014) reported that HSP90 interacts with a BR signaling component, BIN2 kinase, to modulate its nuclear retention. Independently of their study, HSP90 was also found to bind to BES1 (Lachowiec et al, 2013;Shigeta et al, 2014). These findings suggest the involvement and importance of HSP90 activity in BR signaling.…”
Section: Introductionmentioning
confidence: 80%
“…Accordingly, duplicated genes in yeast in which one of the gene copies, but not its paralog, is a client of Hsp90 shows faster evolution at the Hsp90 client copy than its non-client paralog [43]. Moreover, one of the two paralogs of a transcription factor in the brassinosteroid pathway in the plant Arabidopsis thaliana that requires Hsp90 for folding shows more relaxed constraints than its non-client paralog [43]. Since duplicates are considered identical or nearly so at their birth, such results are not artifacts caused by the differential protein stabilities.…”
Section: Hsp90 Canalizes and Capacitates Morphological Variation In Ementioning
confidence: 99%
“…However, BES1 has five predicted gene models encoding two possible proteins based on The Arabidopsis Information Resource (Lamesch et al, 2012;Lachowiec et al, 2013). Sequence analysis indicated that At1G19350.3 arises from an alternative transcription initiation (ATI) at another upstream transcription start site (TSS) and an alternative splicing (AS), thus encoding a longer protein with additional 22 amino acid residues at the N terminus ( Figure 1A).…”
Section: Identification Of Bes1-l In a Thalianamentioning
confidence: 99%
“…To avoid the deleterious effects of mutation, gene duplication events occur to allow one copy of a gene to maintain its function, while another copy may diverge to acquire new functions (Sayou et al, 2014). BES1 and BZR1 belong to a small gene family encoding plant-specific transcription factors, and they may have originated from a common ancestor and then diverged (Yin et al, 2005;Lachowiec et al, 2013). A previous examination of the dN/dS ratio, which is used to infer the direction and magnitude of the effect of natural selection on protein-coding genes, revealed that compared with BZR1, BES1 has been undergoing relaxed purifying selection, suggesting that BES1 may have a more rapid evolution rate.…”
Section: Bes1-l Is a More Recently Evolved Isoform In A Thalianamentioning
confidence: 99%
See 1 more Smart Citation